Educación profesional y sabidurías de los jóvenes campesinos en la Amazonía: una reflexión desde la agroecología política - SOUSA, Romier da Paixão (2015)
The main problems of current mankind are directly related to the ecological crisis and low equity in global level (Funtowicz & Ravetz, 2000; Garrido, 2007 among others). It has been more and more consensus the dominant conception role of science about the ways that have been run this crisis. In this way, young farmers are placed in second plan concerning to industrial agriculture, however they indeed play an important role in food production in a more balanced way and by using less natural resources. The arising of an agriculture more distant from nature is a product that comes from “the great transformation” took place over the last two hundred years, which from a set of social, economical, political and technological changes, it shifts the way society would be related to nature (González de Molina & Toledo, 2011). This process was intensified after Second World War, which is known as “Modernization”, and understood as the “technical agricultural base change due to changes through usage of modern production means by replacing raw materials in industrial production”. Modernization is mainly featured by the demand for increase in agricultural productivity, by inserting changes in genetic base of many plants and animal species, joined to the intensive usege of artificial products such as fertilizers, pesticides, herbicides, irrigation, mechanization (Mussoi, 2011). To carry out this transformation of technical base in agriculture, this conception has been widely assumed by mechanisms of production and knowledge dissemination, associated to funding of farmers. Therefore, training, researching, extension and rural credit have had a fundamental role in spreading this new dominant developed country technology around the world (Mussoi, 2011). Modernization outcomes in popular areas and society in general, have been largely registered (IASTD, 2008). Part of the occurred problems because of this process was the loss of young farmers knowledge. Invisibility and discrimination of this knowledge were also noticed as a modernization product. In this sense, farmers through their social organization have been building around the world hegemonic forms of knowledge dissemination, like education, research and extension based on agroecological principles, social resistance practices and policies. The following thesis aims to analyze influence of professional education rooted on an agroecological approach in the peasantry and repeasantry process of young farmers in rural Amazon.Specific goals are: a) Think over educational role on an agroecological approach in permanence of young people in familiar farms; b) Feature practices and farming innovation developed by young farmers in rural areas of Amazon; c) Analyze how scientific knowledge articulated to young farmers’ knowledge has been providing changes in Agroecosystems. For explore more deeply the reflections it will be tested two hypothesis that dialogue with the theme: I) Education of young farmers by focusing on rural education and agroecological approach provides a peasantry and repeasantry in Amazon from appreciation of knowledge and students’ identities and their influence in production practices at family farms; II) Farmers have been implementing innovation in their family farms in a perspective of building an economical and productive autonomy of lands. The approach of this thesis will be the methodological one of Agroecology policy, cultural Antropology and popular education under a social science point of view, which seeks articulate different concepts that aid to answer research questions. It is a research with a qualitative character – participative action to take data. The work was developed in Brazil, in the State of Pará – Amazon, with young farmers, students from training with agro-ecological approach from 2012-2014. It was interviewed 37 (thirtyseven) people among teachers, youths, social movement members and parents of young farmers in six cities in the state of Pará. It was applied a questionnaire to 80 young farmers concerned to their educational processes, life stories, job relation in family farms, political organization, and their future projects. Firstly, it can be assumed there was a large increase in Agroecology training in Brazil in different levels of teaching. These trainings are quite diverse and with different goals, but generally they have been a product of teachers and researchers’ criticism about modernization standards of agriculture in the country, and the purpose of training professionals to be able to contribute with a look at agricultural sustainability. Concerned to young farmers in Amazon it was realized there was a change in production systems that comes from training they had which is based on agroecological approach. Furthermore, there was an awareness of farming role in society, by influencing these young farmers to stay in the rural environment, as well as thinking of alternatives of production and social organization aiming their social and economic reproduction.